Komodifikasi Media dan Budaya Kohe - Sumartono, Sumartono (Jurnal The Messenger, 2016)
The  mass  media  which  should  serve  as  a  channel  of  information,  entertainment, education, and social control only able to portray itself solely as a medium of information and  entertainment. Business dimension override seemed ideal dimensions that should go hand in hand. Commodification of the media has obscured the real function of the media. On behalf of  the commercialization of value to media converted to market value. Not important quality of a program. Put forward is how a program backed by the financial strength or sponsorship. As a result, the commodification of the media has spawned society commodities. Society tends to be  absorbed in the strength of  an increasingly hegemonic pop culture   with all its  attributes. Lifestyle has become a commodity. Lifestyle embodied in Kohe culture.